OPTIMALISASI PENGEMBANGAN BISNIS PHOTOBOX SEBAGAI PELUANG USAHA KREATIF DI ROYAL BAROE KOTA SERANG - Angger Faiz Aulia Bintang Pratama; Ade Fauji; Amilatussolihah Amilatussolihah; Faridatul Maharani (Yayasan Education and Social Center, 2026)
Community Service (PkM) activities on the optimization of photobox business development as a creative business opportunity were conducted at Royal Baroe, Serang City, in January 2026. The program aimed to improve the knowledge and skills of business partners in managing photobox businesses through observation, socialization, training, mentoring, and evaluation activities. The implementation adopted a participatory and mentoring approach that actively involved business partners in identifying problems and formulating development strategies. The results demonstrated improvements in partners’ understanding of the creative economy concept, digital entrepreneurship, and experience-based business development. Furthermore, partners gained enhanced capabilities in utilizing social media for promotion, developing digital marketing content, and designing innovative service packages. Several service innovations were successfully developed, including family packages, birthday packages, friendship packages, and seasonal-themed packages to increase customer attraction and satisfaction. The mentoring activities also encouraged partners to formulate more systematic and sustainable business development plans. Overall, this community service activity positively contributed to strengthening business capacity, improving competitiveness, and increasing the readiness of photobox entrepreneurs to adapt to market changes. The photobox business at Royal Baroe has significant potential to become a sustainable creative business that contributes to local economic development and promotes the growth of the creative economy sector in Serang City.